2009
DOI: 10.1117/12.825424
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of extended and unscented Kalman, particle, and smooth variable structure filters on a bearing-only target tracking problem

Abstract: In this paper, we study a nonlinear bearing-only target tracking problem using four different estimation strategies and compare their performances. This study is based on a classical ground surveillance problem, where a moving airborne platform with a sensor is used to track a moving target. The tracking scenario is set in two dimensions, with the measurement providing angle observations. Four nonlinear estimation strategies are used to track the target: the popular extended and unscented Kalman filters (EKF/U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Also the accuracy of predictors and the effect of their accuracy on missing rate and energy consumption is considered. So the linear predictor [1], modified version of Kalman filter named EKF which introduced in [22] and another modified version of Kalman filter named UKF [23] are considered to have a fair comparison. Finally the impact of node selection algorithm on network lifetime is investigated.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Also the accuracy of predictors and the effect of their accuracy on missing rate and energy consumption is considered. So the linear predictor [1], modified version of Kalman filter named EKF which introduced in [22] and another modified version of Kalman filter named UKF [23] are considered to have a fair comparison. Finally the impact of node selection algorithm on network lifetime is investigated.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Therefore, a combined variable structure and Kalman filtering approach for parameter estimation has been proposed in [15]. A comparison between the EKF, SVSF, PF, and UKF on a bearing-only target tracking problem was demonstrated in [16]. The results demonstrated that the SVSF yielded accurate state estimates while maintaining robustness to uncertainties.…”
Section: Introductionmentioning
confidence: 94%
“…31,32 A corrective term, referred to as the SVSF gain, is computed as a function of the error in the predicted output, as well as a gain matrix and the smoothing boundary layer width. 30,32,33 The corrected term calculated in equation (21) is then used in equation (24) to find a posteriori state estimate. The priori and posteriori output error estimates are considered as critical variables which are defined by equations (25) and (26), respectively 32,33 The estimation progression makes a summary of equations (21)- (28) and is repeated iteratively.…”
Section: Svsf-slam Algorithmmentioning
confidence: 99%
“…30,32,33 The corrected term calculated in equation (21) is then used in equation (24) to find a posteriori state estimate. The priori and posteriori output error estimates are considered as critical variables which are defined by equations (25) and (26), respectively 32,33 The estimation progression makes a summary of equations (21)- (28) and is repeated iteratively. U k is the input control vector.…”
Section: Svsf-slam Algorithmmentioning
confidence: 99%
See 1 more Smart Citation